Pengaruh Istinsyaq Sebagai Terapi Alternatif Pada Penderita Rinosinusitis Kronik Di Rumah Sakit Ibnu Sina Tahun 2022 - Kesya Azzahra Putri; Mochammad Erwin Rachman; Rachmat Faisal Syamsu; Mohammad Reza Zainal Abidin (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
The aim of this research is to determine the effect of istinsyaq as an alternative therapy on sufferers of chronic rhinosinusitis at Ibnu Sina Hospital in 2022, while the research method used is Pre-Post Experimental research using a one group pre-post test approach without control, by making the first observation (pre-test) which makes it possible to test changes that occur after the experiment by conducting a second observation (post-test). Research results: The level of chronic rhinosinusitis symptom scale that is felt by many samples suffering from chronic rhinosinusitis, whether they have had surgery or not, is included in the severe type scale and moderate type scale categories. Istinsyaq is effectively used as an alternative therapy for chronic rhinosinusitis sufferers in that the scale of symptoms decreases after the intervention is given, there is a decrease in the number of scales.